Discovery Learning Model in Learning Maharah Qira'ah in Senior High School/ Model Discovery Learning pada Pembelajaran Maharah Qira’ah di Sekolah Menengah Atas - Siti Nurilngin (ATHLA : Journal of Arabic Teaching, Linguistic and Literature, 2022)
This research is motivated by the problems experienced by students in studying qiro'ah material. In practice, students often have difficulty understanding reading texts because of the lack of mufrodat vocabulary. The use of inappropriate learning models such as lectures makes students bored, especially if students' reading skills are weak. Unlike the Diponegoro Islamic High School Surakarta students who are enthusiastic when learning qiro'ah because the teacher applies the discovery learning model. The research method used is descriptive qualitative, with data collection techniques of observation, interviews, and documentation of the research subjects of class XI IPS. The purpose of the study was to describe the application of the discovery learning model to the learning of maharah qiro'ah in class XI IPS for Diponegoro Islamic High School students. The results show that the application of the discovery learning model by listening to native speaker audio and discussing can run smoothly and achieve fahmul masmu' and fahmul maqru'.